Media Culture and Higher Education in Bulgaria: Integrating Media and Information Literacy Education in Social Sciences - Svetla Tsankova; Stella Angova; Ivan Valchanov (Проблеми на постмодерността)
This paper examines the main challenges facing the integration of media culture education in higher education in Bulgaria. The authors argue for the choice of "media culture" as a course   name with the provision of theoretical and practical-applied knowledge for the perception and analysis of the impact of various media forms, public communications and types of content in a cultural, social, educational, technological, and economic context. The undergraduate course was introduced during the academic year 2023/24 for the first time in the curriculum of several majors in the field of social sciences to second-year students of the majors "Media and Journalism", "Media Economics", "Sociology", "Political Science", "International Relations" and "European Politics and Economics" at the University of National and World Economy. The effectiveness of the course in terms of acquired knowledge and skills for critical participation in media processes was assessed through an anonymous survey in Microsoft Forms. 76 respondents answered 12 questions – 10 with option choice and 2 with text input. The results reveal that students felt more adapted to the media world and better prepared to distinguish between different types of information, including disinformation and propaganda. The course also increased their confidence in evaluation and usage of media sources, while developing their critical thinking regarding social processes. Students identified topics that should be separately identified in the curriculum. The study allows for the identification of issues for national discussion from the perspective of challenges to the integration of media literacy education in universities, overcoming key barriers to the introduction and development of media literacy-oriented courses, and the impact and effectiveness of media literacy education in higher education institutions in Bulgaria.